SAT0192 MYOSITIS IN PATIENTS WITH PRIMARY SJÖGREN'S SYNDROME: DATA FROM A FRENCH NATIONWIDE SURVEY. (June 2019) - Houssais, Camille; Noury, Jean-Baptiste; Allenbach, Yves; Gallay, Laure; Assan, Florence; Benveniste, Olivier; Broner, Jonathan; Duffau, Pierre; Espitia-Thibault, Alexandra; Grasland, Anne; Sanges, Sebastien; Hayem, Gilles; et al.
Abstract : Background: Myositis is recognized as a manifestation of primary Sjögren's syndrome (pSS). Grading muscle involvement using the EULAR Sjögren Syndrome Disease Activity index (ESSDAI) does not require biopsy-proven active myositis or extensive immunological investigations. However, several studies have reported that a high proportion of pSS-associated myositis is either inclusion body myositis (IBM) or an overlap with idiopathic inflammatory myopathies. Objectives: The objective of our study was to investigate the nature of inflammatory muscle involvement in a large sample of patients with pSS and concurrent myositis. Methods: We conducted a French nation-wide survey among reference centers known for their experience in the field of systemic auto-immune diseases. Patients with physician-based diagnosis of pSS and inflammatory muscle involvement were included. They were categorized and subsequently described and compared according to the identification of an associated condition likely to explain inflammatory muscle involvement. Results: 60 cases of myositis in patients with pSS were identified. Patients were mostly female (52/60) and pSS classification criteria were met in 43/60. Muscle biopsy was performed in 50/60 patients and showed inflammatory lesions in 80% of cases. An associated condition likely to explain myositis was identified in 31 patients: typical dermatomyositis rash (n=8), MCTD-specific antibodies (n=11), myositis specific antibodies (n=10), and systemic lupus erythematosus, scleroderma or ANCA associated vasculitis specific antibodies in favor of an overlap syndrome (n=7). Among the 29 patients without associated condition likely to explain myositis, 17 had a biopsy proven inflammatory muscle disease, showing histopathologic features consistent with IBM in 5 cases. 4 of the 5 patients with IBM histological features received corticosteroids and/or other immunosuppressive agents to treat muscle disease. Worsening of muscular involvement despite treatment was reported in these 4 patients. Comparative analysis showed a lower ESSDAI (p = 0.001) among patients without identified associated condition likely to explain myositis. Conclusion: In most cases of concurrent pSS and myositis, inflammatory muscle involvement is explained by a context of overlap syndrome or has a histological pattern consistent with IBM. Extensive immunological investigations and muscle biopsy appear to be necessary in pSS patients with suspected inflammatory muscle involvement, in order to avoid misclassification and/or overtreatment. Disclosure of Interests: Camille Houssais: None declared, Jean-baptiste Noury: None declared, Yves Allenbach: None declared, Laure Gallay: None declared, Florence Assan: None declared, Olivier Benveniste: None declared, Jonathan Broner: None declared, Pierre Duffau: None declared, Alexandra Espitia-Thibault: None declared, Anne Grasland: None declared, Sebastien SANGES: None declared, Gilles Hayem: None declared, Véronique LE GUERN: None declared, Nihal Martis: None declared, Kuberaka Marianpillai: None declared, Denis Mulleman Speakers bureau: Pfizer, Novartis, Grifols, Gaëtane Nocturne: None declared, alain meyer: None declared, Valerie Devauchelle-Pensec Grant/research support from: Roche-Chugai, Speakers bureau: MSD, BMS, UCB, Roche, Divi Cornec: None declared, Dewi Guellec: None declared